Persia and the Malay World: Commercial and Intellectual Exchanges - Guillot, Claude (Studia Islamika, 2020)
This article endeavours to review all known data about the relations, both direct and indirect, between Persia and the Malay World, from the earliest times up to the 17th century. Very early in the first centuries of our era, during the Sassanid period, we can observe the movements of people and commercial products. Contacts became more important after the rise of Islam. Small Persian communities (merchants and clerics) settled in various harbours of the Archipelago had an influence on Malay culture out of proportion with their number. An influence that is reflected by Persian texts translated into Malay and Javanese, by fragments of Persian Sufi poetry quoted in Malay works, and again by the various roles of Persian thinkers, like for instance the Sufi master Shams Tabrīz, in Malay and Javanese cultures. However, relations started to fade away with the advent of the Safavids and the decline of the Mughal empire.